Trauma and Public Mental Health: A Focused Review - Kleber, Rolf J. (Frontiers in Psychiatry, 2019)
The purpose of this article is to show the relevance of the discipline of traumatic stress studies to the field of public mental health by examining central concepts and findings concerning trauma and its aftermath and examining implications for public mental health. Attention is paid to the diagnosis of posttraumatic stress disorder (description, epidemiology as well as conceptual dilemma’s) and the construct of resilience. Next, the psychological impact of traumatic experiences on the individual and the environment are examined. Besides, the long-term consequences are described as well as the relevant concept of Complex PTSD. Finally, specific areas of public mental health activities are discussed briefly. A public mental health perspective will help to develop preventive approaches to trauma and extend the impact of various forms of interventions. It will also make clear that trauma care will have to consider the community and the society at large.